Black spruce layering is unlikely to achieve canopy closure between regional fire return intervals in Kalmia-black spruce shrub savannah of eastern Canada - Colin St. James; Azim Mallik (Forest Ecology and Management, 2026)

Climate Controls Cold‐ But Not Warm‐Adapted Sphagnum Distribution and Carbon Sink Capacity - Si‐Nan Wang; Jun‐Xiao Ma; Håkan Rydin; Azim Mallik; Zicheng Yu; Meng Wang; Zhongqiu Sun; Zhao‐Jun Bu (Global Change Biology, 2026)
Despite the critical role of Sphagnum mosses in carbon (C) sequestration, it remains unclear how climate governs their distribution and C sink function. To address this, a reciprocal transplant experiment was performed over 2 years in two peatlands in the Changbai Mountains, utilizing moss monolith mesocosms from low‐elevation ( S. imbricatum ), high‐elevation ( S. fuscum ), and wide‐elevation‐range ( S. magellanicum ) Sphagnum species. We found that when low‐elevation Sphagnum populations were transplanted upward, both the non‐structural carbohydrates (NSC) content and photosystem II efficiency (Φ PSII ) increased, with concomitant reduced ecosystem respiration (ER) and enhanced C sequestration at high elevation. In contrast, for high‐elevation populations, downward transplant significantly weakened gross primary productivity (GPP), primarily by reducing Sphagnum photosynthesis and physiological performance, accompanied by slightly enhanced peat decomposition, ultimately suppressing net ecosystem productivity (NEP) by more than 50%. These results indicate that the 4°C temperature difference associated with the elevational gradient does not restrict the upward distribution of warm‐adapted S. imbricatum and S. magellanicum populations, but it severely restricts the downward distribution of cold‐adapted S. fuscum and S. magellanicum populations. Altered vegetation composition and microbial community coincided with NEP changes in ex‐situ transplants. Our study demonstrates that geographical origin, rather than genetic divergence, strongly affects the short‐term performance of Sphagnum under both cooling and warming conditions. Climate thus controls the distribution and C sink capacity of cold‐ but not warm‐adapted Sphagnum , highlighting the vulnerability of cold‐adapted Sphagnum to warming.

No evidence of rhizomatous resource sharing of Kalmia angustifolia in established heath - Azim U. Mallik; Philippe St. Martin (Perspectives in Plant Ecology, Evolution and Systematics, 2026)

Microhabitat-dependent elevational effect on germinability and viability of Sphagnum spores - Jiaqi Zhang; Boli Yi; Shuayib Yusup; Jian-Yi Wang; Bei-Bei Fan; Azim Mallik; Zhao-Jun Bu (Alpine Botany, 2025)

The interactive effect of phenolics and microorganisms on Sphagnum spore viability and germination - Bei-Bei Fan; Azim Mallik; Si-Nan Wang; Jia-Qi Zhang; Jian-Yi Wang; Zhao-Jun Bu (Flora, 2025)

Additions of nitrogen and phosphorus do not reduce storage but stability of soil carbon in a northern peatland - Si-Nan Wang; Xu Chen; Jun-Xiao Ma; Xuan Liu; Azim Mallik; Meng Wang; Shasha Liu; Mingming Zhang; Zhao-Jun Bu (Plant and Soil, 2025)

Acadian forest resilience to clearcutting: implications for even-aged management in late-successional northern temperate forests - Faisal Moola; Philippe St. Martin; Azim U. Mallik; Liette Vasseur (Plant Ecology, 2024)

Drainage-Driven Loss of Carbon Sequestration of a Temperate Peatland in Northeast China - Xu Chen; Azim U. Mallik; Zicheng Yu; Zucheng Wang; Shengzhong Wang; Yanmin Dong; Ming-Ming Zhang; Zhao-Jun Bu (Ecosystems, 2024)

Intraspecific trait variation as a mechanism of coexistence of congeneric blueberry (Vaccinium) species after forest harvesting - Philippe St. Martin; Azim Mallik (Forest Ecology and Management, 2023)

Litter mixing effects on decomposition in a peatland partially drained 30 years ago - Talal Asif; Iqra Naeem; Zhao-Jun Bu; Azim Mallik; Jin-Ze Ma; Line Rochefort (Wetlands Ecology and Management, 2021)

Soil chemistry drives below ground traits in an alternate successional pathway from forest to heath - Philippe St. Martin; Azim U. Mallik (Oecologia, 2021)

Resource competition and allelopathy in two peat mosses: implication for niche differentiation - Chao Liu; Zhao-Jun Bu; Azim Mallik; Line Rochefort; Xue-Feng Hu; Zicheng Yu (Plant and Soil, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Continuous Waterlogging May Not Facilitate Germinability Maintenance of Sphagnum Spores - Lu Feng; Zhao-Jun Bu; Azim Mallik; Zu-Cheng Wang; Sha-Sha Liu; Yu-Huan Wu (Wetlands, 2017)

Belowground interactions between Kalmia angustifolia and Picea mariana: roles of competition, root exudates and ectomycorrhizal association - Azim U. Mallik; Shekhar R. Biswas; Laura C. Siegwart Collier (Plant and Soil, 2016)

Control of Panama Disease of Banana by Rotating and Intercropping with Chinese Chive (Allium Tuberosum Rottler): Role of Plant Volatiles - Hui Zhang; Azim Mallik; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

Ecology of Compounding Disturbances: The Effects of Prescribed Burning After Clearcutting - Keri Pidgen; Azim U. Mallik (Ecosystems, 2013)

Does post-fire abiotic habitat filtering create divergent plant communities in black spruce forests of eastern Canada? - Laura C. Siegwart Collier; Azim U. Mallik (Oecologia, 2010)

Disturbance effects on species diversity and functional diversity in riparian and upland plant communities - Shekhar R. Biswas; Azim U. Mallik (Ecology, 2010)
Understanding disturbance effects on species diversity and functional diversity is fundamental to conservation planning but remains elusive. We quantified species richness, diversity, and evenness and functional richness, diversity, and evenness of riparian and upland plants along 24 small streams subjected to a range of anthropogenic disturbances in the boreal forest of northwestern Ontario, Canada. We included a total of 36 functional traits related to productivity, competitive ability, reproduction, disturbance tolerance, life history, and tolerance to habitat instability. Using nested ANOVA, we examined the response of diversity indices to disturbance and whether it followed the intermediate disturbance hypothesis (IDH) and varied with habitat stability. We found that, like species richness and diversity, functional richness and diversity reached peaks at moderate disturbance intensity; functional diversity followed the predictions of the IDH. Second, disturbance–habitat‐stability coupling has very little effect on overall species and functional diversity, but the effect on particular life forms and functions may be significant. Since species richness and diversity patterns are context and system dependent, our findings should be most applicable to similar temperate riparian systems.

A unified framework for the restoration of Southeast Asian mangroves—bridging ecology, society and economics - Shekhar R. Biswas; Azim U. Mallik; Junaid K. Choudhury; Ainun Nishat (Wetlands Ecology and Management, 2009)

Species and Spacing Effects of Northern Conifers on Forest Productivity and Soil Chemistry in a 50-Year-Old Common Garden Experiment - Azim U. Mallik; M. Kamal Hossain; Eric G. Lamb (Journal of Forestry, 2008)
This study examines the long-term effects of experimental conifer monocultures on stem volume and soil chemistry. Replicated plots of black spruce ( Picea mariana ), white spruce ( Picea glauca ), and red pine ( Pinus resinosa ) were planted in 1950 at three spacings (1.8, 2.7, and 3.6 m) on a briefly cultivated agricultural field on glaciolacustrine sandy loam soil near Thunder Bay, Ontario, Canada. Stem volumes per hectare and per tree were measured in 2002 (52 years after planting). Surface organic (i.e., forest floor) and mineral soil fertility in terms of pH, total N and P, and extractable NH 4 -N and P were measured in 2000 (50 years after planting). Of the three species red pine had the highest volume per hectare at all the three spacing followed by white spruce and black spruce; volume for all three species peaked at the 1.8-m spacing. The effects of conifer species on soil physical and chemical properties were more pronounced than spacing effects and the changes were mainly confined to forest floor layer. Few changes in mineral soil properties occurred because of the species and spacing treatments. Per hectare forest floor nutrient pools were higher under white spruce and red pine than black spruce, a pattern likely driven by higher litterfall and forest floor accumulation. It appears that toward the end of first rotation the higher productivity of red pine compared with the other conifers did not come at the cost of reduced soil pools of available NH 4 , PO 4 , or K, but it was associated with reduced Ca levels in the forest floor.

Relationships between ericaceous vegetation and soil nutrient status in a post-fire Kalmia angustifolia-black spruce chronosequence - Robin G. Bloom; Azim U. Mallik (Plant and Soil, 2006)

Selected Ectomycorrhizal Fungi of Black Spruce (Picea mariana) can Detoxify Phenolic Compounds of Kalmia angustifolia - Ren Sen Zeng; Azim U. Mallik (Journal of Chemical Ecology, 2006)

Indirect effects of black spruce (Picea mariana) cover on community structure and function in sheep laurel (Kalmia angustifolia) dominated heath of eastern Canada - Robin G. Bloom; Azim U. Mallik (Plant and Soil, 2004)

Growth Stimulation of Ectomycorrhizal Fungi by Root Exudates of Brassicaceae Plants: Role of Degraded Compounds of Indole Glucosinolates - Ren Sen Zeng; Azim U. Mallik; Ed Setliff (Journal of Chemical Ecology, 2003)